Educating College Students on Academic Integrity: What Roles do Teachers Play in the Quebec Province? - Déri, Catherine E. (Canadian Perspectives on Academic Integrity, 2023)
Over the past 15 years, there has been a shift from detecting and sanctioning academic misconduct to preventing and promoting desired academic practices (Ferguson et al., 2007). According to Gray and Jordan (2012), teachers represent an influential figure to enhance students’ understanding of academic standards. However, a study conducted by Löfström et al. (2014) reveals that educators do not share the same perspectives on how academic integrity should be taught and whose responsibility it is to teach it. Moreover, Peters et al. (2019) developed a conceptual framework illustrating seven roles adopted by educators when teaching academic integrity, with each end of the spectrum identified as acting as “Ambassador” to being completely “Detached” (p. 6). These two teams of scholars examined the teaching of academic integrity at the university level, but little is known about how this is taught at the college level. This is why we explored the situation in seven colleges[1] across the province of Quebec in Canada. During our communication, we will present results from semi-structured interviews with 17 college teachers. A discussion will follow on winning strategies utilized by college teachers for promoting academic integrity among the student population. Finally, we will recommend further avenues of exploration in the domain of teaching and learning at institutions of higher education to foster a culture of academic integrity. [1] In the Quebec province, colleges are called cégep (collège d’enseignement general et professionnel) to prepare students for university studies or provide them with technical skills to enter the labour market.